2002
DOI: 10.1248/cpb.50.1280
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted Hydroxyureas as Urease Inhibitors.

Abstract: Persons infected with Helicobacter pylori are exposed to a high risk for stomach cancer. As eradication therapy, a combination of antibiotics and a proton inhibitor has been adopted. However, this therapy is unsatisfactory due to the induction of drug-resistance. Thus, the urease activity of H. pylori may be an attractive target for drug design of an anti-H. pylori agent. Hydroxyurea (1), an antineoplastic agent, 1) has been known to inhibit various ureases from microorganisms and vegetables, including H. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 10 publications
(12 reference statements)
0
23
0
Order By: Relevance
“…Compounds 1-12 have been reported elsewhere [31][32][33][34][35][36][37][38][39][40][41][42] using different procedures to those described here.…”
Section: Hydroxamic Acid Synthesesmentioning
confidence: 99%
“…Compounds 1-12 have been reported elsewhere [31][32][33][34][35][36][37][38][39][40][41][42] using different procedures to those described here.…”
Section: Hydroxamic Acid Synthesesmentioning
confidence: 99%
“…Among them, only 2 reacted with hydrogen in the presence of palladium/carbon (Pd/C, 10 %), which resulted in 1-(N-hydroxycarbamoyl)benzotriazole (5) in quantitative yield. Uesato et al (16) reported the use of benzyloxyisocyanate as a useful building block in the synthesis of hydroxyurea derivatives, while Butula and Jadrijevi}-Mladar Taka~ (14) reported that 2, when heated over 100°C liberates benzyloxyisocyanate which is further trimerized to N,N',N''-tribenzyloxy-triazinone (10), and yields a minor product N,N',N''--tribenzyloxybiuret (11). In this work, we utilized 2 as a donor of benzyloxyisocyanate, which is very useful for the synthesis of hydroxyurea derivatives.…”
Section: Chemistrymentioning
confidence: 99%
“…The corresponding hydroxyl derivatives, i.e., 1-(Nhydroxycarbamoyl)benzotriazole (5), N-hydroxybiuret (12) (20), 4-{[(hidroxy)carbamoyl]amino}benzoic acid (13), N-hydroxurea (14), N,N',N''-trihydroxybiuret (15) (20) and N,N',N''-trihydroxyisocyanuric acid (16) were obtained in quantitative yields. The synthetic routes and structures of isolated compounds are presented in Scheme 1, whereas their physicochemical data are summarized in Tables I and II. The synthesized set of compounds (Table I) represents different derivatives of hydroxyurea, which can be categorized into several subgroups, i.e., benzotriazole N-carbamoyl derivatives (2, 3, 4 and 5), cyclic-(10, 16 and 17) and acyclic hydroxyurea derivatives (7, 8, 9, 13 and 14), and biuret derivatives (6, 11, 12 and 15).…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations